PENGEMBANGAN ASESMEN BERBASIS KURIKULUM MERDEKA ELEMEN 6 MATA PELAJARAN DASAR-DASAR PEMASARAN BERBANTUAN QUIZIZZ DI SMK NEGERI MOJOAGUNG - Mulyawan, Arip; Dwijayanti, Renny (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
Educational curriculum changes in vocational high schools (SMK) require adaptation in their implementation in the learning process, as in learning assessment activities. In class X Digital Business at SMK Negeri Mojoagung, teachers have not adapted learning assessment activities based on the curriculum used and have not been adjusted to the characteristics of students. Research on the development of assessment based on the kurikulum merdeka on element 3 of the subject basics of marketing assisted by quizizz at SMK Negeri Mojoagung aims to know the development, feasibility and response of students to the kurikulum merdeka-based assessment assisted by quizizz. This research type using research and development (research and development) with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The subject of the trial was students of class X Digital Business 3 of SMK Negeri Mojoagung. The research instruments used interview forms, expert review and validation sheets, and learner response forms. Data analysis techniques using descriptive qualitative analysis of interview forms and expert reviews, while expert validation sheets and learner responses were analyzed quantitatively with percentages. The results of the research used the ADDIE development model. The assessment feasibility by material experts is 90% with very feasible criteria, assessment experts are 96.36% with very feasible criteria, and linguists are 90% with very feasible criteria. Students' responses to the developed assessment have very feasible criteria with a score of 89.72%. The developed assessment is feasible to use and got a positive response from students. Keywords : Assessment; Kurikulum merdeka; Marketing basics; Quizizz